ESTUDIO PRELIMINAR DE LA ASOCIACIÓN ENTRE ESPECIES DE BOMBUS (HYMENOPTERA: APIDAE) Y LA FLORA DEL BOSQUE SERRANO EN CÓRDOBA (ARGENTINA) - Sosa, Claudio Alejandro (Acta Entomológica Chilena, 2022)
This preliminary study reports the relationship between bumblebees and flowers of the Bosque Serrano in Córdoba, Argentina. There are three species of Bombus present in the area: moño, opifex and bellicosus Observations were made on the behavior of pollinators and flower syndromes. The results show that each species of bumblebees presented a specific behavior when a particular plant was visited, but there are no differences between specimens.